MENINGKATKAN KETERAMPILAN PEMASARAN DIGITAL BAGI ANGGOTA PERTUBUHAN MASYARAKAT INDONESIA (PERMAI) PULAU PINANG MALAYSIA: Meningkatkan Keterampilan Pemasaran Digital untuk Anggota Pertubuhan Masyarakat Indonesia (PERMAI) Pulau Pinang, Malaysia - Arief Bowo Prayoga Kasmo; Heliantono Heliantono; Diah Fistiani Sukardiman; Khozaeni bin Rahmad (Universitas Muhammadiyah Bengkulu, 2024)
The Indonesian Community Organization (PERMAI) in Penang, Malaysia, supports a diverse array of MSMEs known for their high-quality food, beverages, and handicrafts. To sustain their growth, these MSMEs must embrace digital marketing. Currently, many rely on outdated manual methods and have limited exposure to digital tools, which hinders their market reach and strategic optimization. In today’s digital age, mastering digital marketing is essential for these businesses to remain competitive and unlock their full potential. The program focuses on three primary goals: (1) Skill Development: Empower MSME entrepreneurs with key digital marketing skills, such as SEO, social media marketing, content creation, and data analytics; (2) Technology Integration: Transition MSMEs from manual to digital marketing systems, enabling effective use of digital tools and platforms; (3) Competitive Edge: Enhance the competitiveness of MSMEs in Penang by equipping them with the knowledge and skills to implement impactful digital marketing strategies. Targeted outcomes include hosting hands-on workshops tailored to MSME needs, providing ongoing support and mentorship, and sharing success stories and best practices through scientific publications and media. By addressing the need for digital marketing skills and setting clear goals, this program aims to boost the digital marketing capabilities of MSMEs in Penang, ensuring their sustained growth and competitive edge.Keywords: Digital Marketing; MSMEs; Technology Integration